Creative Thinking for PJBL Approach Non-Parametric Analysis - Mujiansyah Muji (JISAE (Journal of Indonesian Student Assessment and Evaluation))
Based on the 2018 PISA results, Indonesia ranked creative thinking at 74th place out of 79 countries. This data shows how important it is that creative thinking needs to be fostered, taught and developed in students. There is a very important approach to developing this capability, namely the PjBL approach by utilizing digital libraries. Such as Google Scholar and Crossref, systematic literature reviews, especially on PGMI UIN Antasari Banjarmasin students. The research results show that with PjBL creative thinking, PGMI UIN Antasari Banjarmasin students are not significantly different from conventional methods in training students' creative thinking if the learning sources are the same, namely Google Scholar and Crossref for discussing science subjects, but the pre-test and post-test results show differences. in student thinking, after using the PjBL approach.